Legal aspects of the activities of the European Union in the field of consumer protection and microeconomic analysis of consumer - Akhmetova, Aliya (Riga Graduate School of Law, 2021)
The aim of this research is a comprehensive study of the legal aspects of the activities of the European Union in the field of consumer protection as one of the independent spheres of the internal policy of this integration organization. The subject of this study is the provisions of the constituent treaties and the legislative acts of the European Union issued on their basis, as well as the developing and complementary legal acts of the EU institutions, the legal positions of the Court of Justice of the European Union on consumer protection, and the norms of international treaties and agreements in which it participates. The object of this study is social relations arising on the basis of the above-mentioned sources of law of the European Union, as well as practical problems of their implementation.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Consumer protection